IMAGING DIAGNOSIS—DUODENOBILIARY REFLUX OF BARIUM SULFATE DURING ESOPHAGOGASTROGRAPHY IN A DOG. Issue 3 (26th July 2014) - Shaikh, Layla; Sharma, Ajay; Secrest, Scott
<x xml:space="preserve">Abstract</x> A 4‐year‐old Australian cattle dog presented for regurgitation, 2 months after duodenal resection and anastomosis for a perforated duodenal ulcer. Duodenobiliary reflux of barium sulfate suspension was detected during fluoroscopic esophagogastrography. Follow‐up radiography 2 hours later demonstrated persistence of the barium in the gallbladder and biliary tree. Ultrasonography showed an open sphincter of Oddi but no other morphological abnormalities with the gallbladder or biliary system. No side effects or bloodwork abnormalities were noted. This is the first case report of duodenobiliary reflux of barium in a dog. The pathophysiology of this phenomenon and its incidence and significance in human medicine are discussed.